Change in citizenship and social science education in (post)war time - Kopińska, Violetta; Açıkalın, Mehmet (JSSE - Journal of Social Science Education, 2024)
According to the Global Conflict Tracker (https://www.cfr.org/global-conflict-tracker), there are currently 27 conflicts in the world, which vary in type and status. In contrast, the Rule of Law in Armed Conflict Online Portal (RULAC), which defines armed conflicts under international humanitarian law, indicates that it is currently monitoring more than 114 armed conflicts in the world (https://geneva-academy.ch/galleries/today-s-armed-conflicts). Some of these conflicts are in the headlines; others are not. However, they all change the lives and functioning of people living there or those who neighbour them. How does education respond to current, future, and past armed conflicts?